2001
DOI: 10.1098/rspb.2000.1399
|View full text |Cite
|
Sign up to set email alerts
|

Sexual conflict and the evolution of female mate choice and male social dominance

Abstract: Con£icts between the sexes over control of reproduction are thought to lead to a cost of sexual selection through the evolution of male traits that manipulate female reproductive physiology and behaviour, and female traits that resist this manipulation. Although studies have begun to document negative ¢tness e¡ects of sexual con£ict, studies showing the expected association between sexual con£ict and the speci¢c behavioural mechanisms of sexual selection are lacking. Here we experimentally manipulated the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 40 publications
2
113
1
Order By: Relevance
“…Furthermore, the reduced fitness in inbred mice is related to the reduced survivorship of males in competitive conditions (Meagher et al 2000). Thus, male competitive behaviour could have evolved secondary to female mate choice (Moore et al 2001) on the basis of the same MHC-related regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the reduced fitness in inbred mice is related to the reduced survivorship of males in competitive conditions (Meagher et al 2000). Thus, male competitive behaviour could have evolved secondary to female mate choice (Moore et al 2001) on the basis of the same MHC-related regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…heterozygote and rare allele advantage, inbreeding avoidance; reviewed by Eklund 1994 andPenn &Potts 1999). However, while sexual selection is traditionally considered to include inter-and intrasexual components (Moshkin et al 2000;Moore et al 2001;Olsson et al 2003), it has not been shown whether the MHC also contributes to male competitive behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Some evolutionary phenomena that were previously explained by mate choice may be better explained by coevolution of males and females resulting from conflicts of interest between the sexes over control of copulation and fertilization (Parker, 1979;Chapman et al, 1995Chapman et al, , 2003Rice, 1996;Alexander, Marshall & Cooley, 1997;Holland & Rice, 1998Rice & HoUand, 1999;Johnstone & Keller, 2000;Michiels, 1998;Gavrilets, Arnqvist & Friberg, 2001;Pitnick, Brown & Miller, 2001 a;Pitnick, Reagan & Holland, 2001 ¿;Stutt & Siva-Jothy, 2001; Moore et al, 2001). These recent discussions emphasize one particular class of direct benefits that a female could derive from resisting male sexual behaviour: avoidance of male-inflicted reductions in her ability to produce offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Most males are able to produce a spermatophylax that exceeds this threshold and therefore typically avoid sperm competition when mating with a virgin female [42]. Sperm competition is not completely eliminated by this mechanism, however, as females can remate after the parturition of their first clutch [40,41] and can store sperm for their entire lifespan [41,42]. There is already compelling evidence that sperm production is costly in N. cinerea.…”
Section: Introductionmentioning
confidence: 99%
“…Male N. cinerea produce a complex ejaculate (the spermatophore) consisting of sperm enclosed in a membranous sac (the ampulla) that is embedded in a gelatinous, proteinaceous mass (the spermatophylax) [40]. If the spermatophylax is above a threshold size, it stimulates a stretch receptor in the female bursa copulatrix that inhibits remating behaviour [35,41,42]. Most males are able to produce a spermatophylax that exceeds this threshold and therefore typically avoid sperm competition when mating with a virgin female [42].…”
Section: Introductionmentioning
confidence: 99%